PENGARUH KELUARGA TERHADAP PERILAKU TUAN DARCY DAN ELIZABETH BENNET DALAM NOVEL PRIDE AND PREJUDICE (PENDEKATAN PSIKOLOGI) - RUGIAN, IREINE PINGKAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT The title of this research is â€œThe Effect of Family toward Mr. Darcy and Elizabeth Bennetâ€™s Behaviorâ€. The objectives of this research are to identify and describe the effect of family in Pride and Prejudice to analyze the influences of family toward Mr. Darcy and Elizabethâ€™s Behaviors. The data are collected by focusing on the role of family toward Mr. Darcy and Elizabeth Bennet and what is the influence to their behavior. The method used in this research is descriptive method and which apply intrinsic and extrinsic approach in analyzing the data.Â The writer uses Psychological theory to identify Mr. Darcy and Elizabeth behaviorâ€™s. The purpose of this research is to show the role of family in Pride and Prejudice especially, Mr. Darcy and Elizabethâ€™s behavior and the effect of family toward their behavior. The result of this research shows that the effect of family has a big influence to Mr. Darcy and Elizabeth Bennetâ€™s behavior. Â Keywords: The effect of family, psychological theory and Pride and Prejudice.